Weakly quasi $(τ_1,τ_2)$-continuous multifunctions (European Journal of Pure and Applied Mathematics, 2024)
Our main purpose is to introduce the notion of weakly quasi $(τ_1,τ_2)$-continuous multifunctions.Furthermore, several characterizations of almost quasi $(τ_1,τ_2)$-continuous multifunctions are established.
Keywords: $τ_1τ_2$-open set; weakly quasi $(τ_1,τ_2)$-continuous multifunction